Development of the Tooth Protection Model as an Action for Caries-Free and Early Stunting Prevention - Rismayani, Lina; Kamelia, Emma; Kristiani, Anie; Astuti, Anjar (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Rampant caries in toddlers or early childhood caries (ECC) can affect chewing and the ability to eat and drink. The prevalence of caries in the 3-4 year age group in Indonesia in 2018 was 81.5%. A recent World Health Organization (WHO) report stated that dental caries can affect children's growth. Balanced evidence shows that ECC is associated with stunting in children. Rampant caries in primary teeth hurt nutritional status, mediated by caries depth, chronic inflammation, and oral pain. A dental and oral health caries prevention program is needed to prevent stunting. This research aims to develop and test the feasibility of a Tooth Protection Model for Preventing Caries and Stunting in Early Childhood. The research method used is Research and Development/ (R&D), consisting of searching for potential problems, collecting data through literature review and FGD, Design Making, Validation of three preventive dentistry experts and three pediatric dentistry experts, Revision and User Feasibility Test for 30 toddler mother. Data analysis uses an Interclass Correlation Coefficient (ICC) with a two-way mixed type. The results of expert validation obtained an average score of 75 (decent category with revision), with good inter-rater reliability (ICC = 0.750). The results of user trials on 18 mothers of toddlers produced an average score of 90.67 (very feasible category without revision), with an ICC value of 0.860, meaning good reliability. The research conclusion shows that the Tooth Protection Model is worthy of implementation as a comprehensive approach to preventing caries and stunting in toddlers.